New Old World Andrena species, with a focus on Turkey (Hymenoptera: Andrenidae) - Wood, Thomas James (Zootaxa, 2023)
Andrena is the second most speciose genus of bees, but much taxonomic work is still required to describe taxa from its centre of diversity—the Old World Mediterranean basin including Turkey to Central Asia—as well as to resolve nomenclatural issues. An additional 16 new species discovered in museum collections are described here: Andrena (Taeniandrena) laevicorpus spec. nov. and Andrena (Ulandrena) graciliata spec. nov. from Cyprus; Andrena (Taeniandrena) taedium spec. nov. from Greece, Turkey, Lebanon, and Iran; Andrena (incertae sedis) maharashtra spec. nov. from India; Andrena (Leimelissa) claves spec. nov. from Kazakhstan; Andrena (Hoplandrena) cephalgia spec. nov. from Kazakhstan, Kyrgyzstan, and Tajikistan; Andrena (Habromelissa) angustula spec. nov. from Mongolia; Andrena (Tarsandrena) palliata spec. nov. from Mongolia & China; and Andrena (Graecandrena) peculiaris spec. nov., Andrena (incertae sedis) colatorium spec. nov., Andrena (incertae sedis) discordia spec. nov., Andrena (incertae sedis) orichalcum spec. nov., Andrena (Melandrena) nox spec. nov., Andrena (Margandrena) cilicia spec. nov., Andrena (Notandrena) ayna spec. nov., and Andrena (Notandrena) taurus spec. nov. from Turkey. A lectotype is designated for Andrena (Avandrena) heterodoxa Pérez, 1903 sp. resurr. which is recognised as the senior synonym of A. (Avandrena) siciliana Warncke, 1980 syn. nov. Andrena (Andrena) bulgariensis Warncke, 1965 is synonymised syn. nov. with A. (Andrena) inconstans Morawitz, 1877. Andrena (Hoplandrena) schoenitzeri Gusenleitner, 1998 is synonymised syn. nov. with A. (Hoplandrena) rosae Panzer, 1801. Andrena (Truncandrena) medeninensis usura Warncke, 1967 is synonymised syn. nov. with A. (Truncandrena) pareklisiae Mavromoustakis, 1957. The female of A. (Chlorandrena) tricuspidata Scheuchl, 2010 and the males of A. (Poecilandrena) adjacens Morawitz, 1875, A. (Aciandrena) palmyriae Wood, 2021, and A. (Tarsandrena) sarydzhasi Osytshnjuk, 2005 are described for the first time. Lectotypes are designated for Andrena (Melandrena) metallica Radoszkowski, 1876 (=Andrena metallescens Cockerell, 1906) and Andrena (Leimelissa) mimetes Cockerell, 1929. Eighteen additional Andrena species are reported from Turkey for the first time, emphasising its status as the likely centre of diversity for this hyper-speciose genus.